(untitled) (American Journal of Islam and Society, 1995)
It is commonly believed that physical phenomena can be understood in scientific terms. Science is presumed to produce knowledge that enables man to predict future events, control his environment or explain diverse phenomena. Regardless of the use to which scientific knowledge is put, the cognitive claim is there. The question is: Do scientific results constitute knowledge? To answer this question, it is necessary to examine the logical structure of science. The problem is one of justification. Given that a conclusion is supported by scientific evidence, is the scientific concept of evidence a legitimate one? These questions about the foundation of scientific inference (i.e., the scientific method of justification) have great import. The methods of inference taught in the Qur’an are distinct from and in conflict with those of science. Furthermore, we believe that the application of the Qur’anic methods will yield knowledge of God, which is the only true knowledge. However, the successes of science and its technological consequences have made many people, including believers in God, equate knowledge with scientific knowledge. There are many who still hold that religion is a matter of faith-the "dogmas" of religion are accepted on faith. The point is that the grounds for accepting a faith have nothing to do with cognitive claims. If a particular religion is fundamentally a matter of faith, then there is no basis for pref erring it to other faiths. In the face of this conflict between the method of the Qur’an and that of science, it is essential to assess the cognitive claims of religion. If our commitment to religion is to be more than an unjustified devotion, we must know that revelation is better suited to the attainment of knowledge than science. The problem is to ascertain whether there are sound logical reasons for supposing that the conclusions of revelation constitute more reliable, in fact the reliable knowledge, than conclusions established on the basis of the scientific method of inferences. Why and How Questions: An Artificial Division Science is based on causality, the cornerstone of materialism and the antithesis of God’s Oneness (tawbid). For this reason, if the scientific ...